Quantification of the loss of well-being associated with the imposition of restrictions on portfolio optimization of retirement-fund managers - Accinelli, Elvio; Piria, Alfredo; Tempone, Raúl (Estudios Económicos de El Colegio de México, 1999)
The restrictions imposed by the regulatory authorities on the composition of retirement-fund portfolios are aimed at avoiding opportunistic behavior on the part of retirement fund managers. However, these restrictions reduce the welfare of the shareholders of such funds. In this paper, the welfare loss associated with different possible restrictions is quantified. In order to do this, we apply efficient mathematical programming techniques to quickly obtain optimal portfolios given these exogenous constraints. We include a numerical example in order to make the effect of such constraints more clear.